PEGARUH KINERJA PEGAWAI KEBUN TERHADAP PENINGKATAN HASIL PRODUKSI BAWANG MERAH (ALLIUM CEPA L.) DI KEBUN PRAKTEK FAKULTAS TEKNOLOGI PANGAN PERTANIAN DAN PERIKANAN UNIVERSITAS NUSA NIPA KELURAHAN KOTA UNENG KECAMATAN ALOK KABUPATEN SIKKA - Bobo, Almerto; Anggriani, Yohana; Yakob Da Rato, Yoseph (Jurnal Biogenerasi, 2025)
This research aims to analyze the influence of plantation employee performance on increasing shallot production yields in the Practical Garden of the Faculty of Food Technology, Agriculture and Fisheries, Nusa Nipa University. The research method used is a quantitative method. The population in this research is workers/garden employees and shallot consumers in the Practical Garden of the Faculty of Food Technology, Agriculture and Fisheries, Nusa Nipa University, Maumere. Respondents in this study were 32 respondents. Data analysis was carried out using a simple linear regression analysis technique. The results of the research showed that based on a simple linear regression analysis test, the results of the equation were with a constant value of 43.030, which means that the consistency value of the variable Influence on Farm Employee Performance was 43.030, the X regression coefficient was 0.253, which states that the addition of 1% value The performance of plantation employees will increase the yield of shallot production by 0.253. The regression coefficient is positive, so it can be said that the direction of influence of Garden Employee Performance (variable X) on Increasing Red Onion Production (variable Y) is positive. And based on the significance value obtained of 0.000 < 0.05, it can be concluded that the variable Influence of Garden Employee Performance (X) has a positive effect on the variable Increase in Red Onion Production Results (Y).